2006
DOI: 10.1007/s00203-006-0106-8
|View full text |Cite
|
Sign up to set email alerts
|

Inducible transcription of genes involved in taurine uptake and dissimilation by Silicibacter pomeroyi DSS-3T

Abstract: A largely untested hypothesis for the bacterial dissimilation of taurine was explored in Silicibacter pomeroyi DSS-3, whose genome has been sequenced. Substrate-specific transcription of candidate genes encoding taurine uptake and dissimilation (tauABC, tpa, ald, xsc, pta) was found, which corresponded to the induction of Tpa, Ald, Xsc and Pta, that was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…strain 217 (2) and R. pomeroyi DSS-3 (14) utilized (S)-cysteate quantitatively, but neither organism utilized sulfolactate extensively (i.e., ϳ10%). Strains 217 and DSS-3 involve Xsc in taurine metabolism, as observed previously (2,21). Roseobacter sp.…”
Section: Mkat (Kg Protein)supporting
confidence: 76%
“…strain 217 (2) and R. pomeroyi DSS-3 (14) utilized (S)-cysteate quantitatively, but neither organism utilized sulfolactate extensively (i.e., ϳ10%). Strains 217 and DSS-3 involve Xsc in taurine metabolism, as observed previously (2,21). Roseobacter sp.…”
Section: Mkat (Kg Protein)supporting
confidence: 76%
“…The regulator, TauR has been associated with (1) taurine degradative genes since their discovery (e.g., Ruff et al 2003;Brüggemann et al 2004;Denger et al 2006;Gorzynska et al 2006;Baldock et al 2007), with (2) assimilation of taurine nitrogen in R. palustris CGA009 (Denger et al 2004b) (where the same genes [RPB_1035-RPB_1039] are found in R. palustris strains HaA2 and TIE-1), and with (3) assimilation of taurine sulfur, where direct evidence of the function of TauR as a regulatory protein is available (Wiethaus et al 2008). We detected two tauR-like genes (MED92_03198 (tauR2) and MED92_13211 (tauR1)) in the genome of N. caesariensis MED92, and we provisionally annotated the eight open reading frames (ORFs) in the flanking regions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a) is apparently initiated by an ABC transporter for taurine (Table 2, Fig. 4), which is widespread (e.g., Eichhorn et al 2000;Gorzynska et al 2006). There is support for the presence of both Tpa1 and Tpa2 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taurine is utilized by environmental bacteria under various metabolic situations (reviewed in reference 6), e.g., as a carbon, nitrogen, and energy source for aerobic heterotrophic growth via the taurine degradation pathway, which has been studied in great detail, including the desulfonation reaction involved (7)(8)(9). At least one bacterium, the marine strain Ruegeria pomeroyi DSS-3, is known to utilize also HT as a source of carbon, nitrogen, and energy (10). However, the HT degradation pathway, and particularly the desulfination reaction involved, remained undefined.…”
mentioning
confidence: 99%